2010
DOI: 10.1007/s00449-010-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring fermentation parameters during phytase production in column-type bioreactor using a new data acquisition system

Abstract: Fermentation parameters for phytase production in column-type bioreactor were monitored using a new data acquisition system. There are a number of studies reporting phytase production in flasks, but a lack of data about microorganism respiration behaviour during phytase production using column bioreactor. The objectives of this work were the monitoration of fermentation parameters during phytase production and its relation with fungal growth and forced air. Phytase production by A. niger FS3 increased with for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Phytase activity was determined by quantification of the phosphate released from phytate during an enzymatic reaction using the ammonium molybdate method with modifications described by Spier et al (2010). Sodium acetate buffer (350 μL, 100 mM, pH 4.5) containing sodium phytate (875 nmol) was used as substrate.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…Phytase activity was determined by quantification of the phosphate released from phytate during an enzymatic reaction using the ammonium molybdate method with modifications described by Spier et al (2010). Sodium acetate buffer (350 μL, 100 mM, pH 4.5) containing sodium phytate (875 nmol) was used as substrate.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…It is worth noting that the gas sampler proposed in our work has some advantages compared to previous designs: a) no gas chromatograph, solenoid or other expensive valves are required, b) the multiplex gas sampler has 24 sample ports, c) the sampling ports can be enabled or disabled as columns are added or retired from the fermentation system, and d) the sampler was designed and built in our laboratory with commercial low cost mechanical and electronic components. Spier et al (25) designed a data acquisition system for monitoring phytase production in SSF. Their system was able to monitor O 2 , co 2 , temperature, volumetric flow rate and relative humidity; however, it could only be used for one column, limiting its use in the optimization of fermentative processes.…”
Section: Experimental Gas Sampler Validationmentioning
confidence: 99%
“…A gas sensor system based in a commercial 16-position flow-through valve was used in SSF bioreactors (17,18). Spier et al (25) designed a data acquisition system for monitoring phytase production in SSF. This system was used to determine O 2 , co 2 , temperature, volumetric flow rate and relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…The project has been used in bioprocesses experiments such as phytases production by solid state fermentation (SSF) [26]. Also, a test conducted with data from submerged fermentation showed the methods used, resulting in very close values of the estimated and calculated by other means [23].…”
Section: Description Of Fersol2mentioning
confidence: 99%
“…Case 1: Relation of enzyme production and fungal growth in column-type bioreactor for SSF Spier et al [26] reported the relation between phytase production and fungal growth during solid state fermentation in column-type bioreactor monitored by Fersol2 data acquisition system (Fig. 9).…”
Section: Applications Of Fersol2 System Already Reportedmentioning
confidence: 99%